Increasing Medical Student Exposure to Neurosurgery: The Educational Value of Special Study Modules, Student Selected Components, and Other Undergraduate Student Projects - Tiefenbach, Jakov; Kaliaperumal, Chandrasekaran; Demetriades, Andreas K. (Frontiers in Surgery, 2022)
Objectives Neurosurgery is a tertiary specialty, and exposure to medical students limited. One way to increase engagement and offer experience in neurosurgery is through Student Selected Components (SSC), Special Study Modules (SSM), or independent projects. Our aim was to assess the educational value of such projects and evaluate their effectiveness in exposing students to the field. Methods A survey was designed and distributed to Edinburgh University medical students and alumni who completed a neurosurgical project within the last 5 years. The survey was anonymous and collected responses over a fortnight. The results were analyzed in Microsoft Excel 2020 Software. Results Twenty-four respondents completed the survey −42% were students and 58% junior doctors. Respondents overwhelmingly enjoyed their project (96%) and reported increased interest in neurosurgery (62%). The project helped improve their knowledge of neurosurgical procedures, pathologies, and/or clinical presentations and allowed connections with the local department. On a Likert scale, 37% felt they gained a good insight into the field. Only 33% felt the project was a good “taster” for the specialty. This is reasonable given that 92% of projects focused on data analysis, and none were designed as clinical attachments. A large number of students had their work published (50%) and presented at conferences (55%). Conclusion Lack of exposure to neurosurgery at medical school is a known limitation within a busy curriculum. Selected Components/Special Study Modules/independent projects help students learn about certain aspects of neurosurgery and raise their level of interest. A majority of participants either achieved presentation at conferences or published their work. However, our results suggest neurosurgical projects complement but do not replace traditional clinical attachments in providing insight into the craft of this specialty.